2007
DOI: 10.1007/s10936-006-9044-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Development in the Speech of a Persian–English Bilingual Child

Abstract: The present study aims at testing the two dominant hypotheses regarding the development of inflections and other functional categories namely the Structure-Building Model and the Continuity Hypothesis within the generative theory. According to the first view, functional categories are entirely absent in children's early grammars, which contain only projections of lexical categories, most importantly 'nouns' and 'verbs.' This hypothesis holds that utterances produced by children are actually small clauses or ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The study aimed to examine the English narrative skills of Persian-English bilingual children and adds to the small body of research on the oral language skills of Persian-English bilingual children [26][27][28]56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study aimed to examine the English narrative skills of Persian-English bilingual children and adds to the small body of research on the oral language skills of Persian-English bilingual children [26][27][28]56].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also found differences in development. For example, a Persian-English bilingual child in Iran developed specific morphemes earlier in Persian than English [28].…”
Section: Persian and Persian-english Bilingualismmentioning
confidence: 99%
“…In doing this, my study draws on the language socialisation and te reo Māori literature discussed above, and also on LA research, and BFLA research, which is reviewed below. Lanza, 1998;Paradis & Navarro, 2003; re Persian/English: Keshavarz, 2007), and comparing acquisition across languages (see, for example, Slobin, 1982). The selection of LA studies that are discussed below have a direct relevance to my study.…”
Section: Studies Of Children Learning Te Reo Māorimentioning
confidence: 99%
“…R. Brown also drew attention to the lack of function words -and therefore functional categories -in early L1-English children's production. More recently, Keshavarz (2007) analysed two-word and multi-word utterances gathered via diary study from a Persian-English bilingual child aged between 16 and 23 months. Keshavarz found that by focussing his analysis on two-morph combinations, rather than two-word combinations, some functional categories of English (e.g., plural -s) and Persian (e.g., copula -e)…”
Section: Combinations Of Two Words or Morphsmentioning
confidence: 99%